GENDER DIFFERENCE IN JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Singh, Rakhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Paper zeroes in upon the different treatment being meted out to the women folk and racial minorities which is what stymies the growth and potential of them in a workplace and a career. The paper further investigates that Women also lag behind in terms of a gender pay gap which is sometimes not discernible but does exist in certain sectors. Also, then there is the tendency of the companies to recruit women in softer roles of the order of the Human Resource management departments which further delimits the broad and comprehensive span of their work and their wider contributions to the organization. How gender plays a key role in the designations of women workers, labour force is a highlight of the narrative of the paper